Comparison between Onlay vs Sublay Mesh Techniques in Terms of Wound Infection, Seroma Formation and Recurrence-A Retrospective Study - Muhammad, Faizan; Hussain, Muhammad Irshad; Bokhari, Syed Muhammad Saud Ali; Akram, Sarmad; Ilyas, Muhammad Haseeb; Shahzad, Khuram; Khan, Muhammad Naqash (Indus Journal of Bioscience Research, 2025)
Introduction: Ventral hernia repair remains a significant challenge, with onlay and sublay mesh techniques being widely used. This study evaluates these approaches in terms of wound infection, seroma formation, recurrence, and skin necrosis. Objectives: To compare the outcomes of onlay and sublay mesh repair techniques in ventral hernia surgery. Materials and Methods: A retrospective cross-sectional study was conducted at Recep Tayyip Erdogan Hospital, Muzaffargarh, reviewing 123 patients who underwent elective mesh hernioplasty from January 2017 to December 2021. Data on demographics, comorbidities, hernia type, procedure type, operative time, and complications were analyzed. Results: Onlay repair was performed in 59.3% and sublay in 40.7% of cases. Seroma formation was higher in sublay (18%) than onlay (10%). Recurrence occurred only in the onlay group (2.86%). SSI rates were 4.3% for onlay and 0% for sublay. Operative time was longer for sublay repairs. Conclusion: We concluded in ths study that both the techniques are effective with comparable outcomes. Sublay repairs reduce recurrence but require longer operative times.